Nutrient Exposure Alters Microbial Composition, Structure, and Mercury Methylating Activity in Periphyton in a Contaminated Watershed - Carrell, Alyssa A.; Schwartz, Grace E.; Cregger, Melissa A.; Gionfriddo, Caitlin M.; Elias, Dwayne A.; Wilpiszeski, Regina L.; Klingeman, Dawn M.; Wymore, Ann M.; Muller, Katherine A.; Brooks, Scott C. (Frontiers in Microbiology, 2021)
The conversion of mercury (Hg) to monomethylmercury (MMHg) is a critical area of concern in global Hg cycling. Periphyton biofilms may harbor significant amounts of MMHg but little is known about the Hg-methylating potential of the periphyton microbiome. Therefore, we used high-throughput amplicon sequencing of the 16S rRNA gene, ITS2 region, and Hg-methylation gene pair (hgcAB) to characterize the archaea/bacteria, fungi, and Hg-methylating microorganisms in periphyton communities grown in a contaminated watershed in East Tennessee (USA). Further, we examined how nutrient amendments (nitrate and/or phosphate) altered periphyton community structure and function. We found that bacterial/archaeal richness in experimental conditions decreased in summer and increased in autumn relative to control treatments, while fungal diversity generally increased in summer and decreased in autumn relative to control treatments. Interestingly, the Hg-methylating communities were dominated by Proteobacteria followed by Candidatus Atribacteria across both seasons. Surprisingly, Hg methylation potential correlated with numerous bacterial families that do not contain hgcAB, suggesting that overall microbiome structure of periphyton communities influence rates of Hg transformation within these microbial mats. To further explore these complex community interactions, we performed a microbial network analysis and found the nitrate amended treatment resulted in the highest number of hub taxa that also corresponded with enhanced Hg-methylation potential. This work provides insight into community interactions within the periphyton microbiome that may contribute to Hg cycling and will inform future research which will focus on establishing mixed microbial consortia to uncover mechanisms driving shifts in Hg cycling within periphyton habitats.